Rethinking the Regional Security Complex Theory: A South American view between 2008-2016 - Ferreira Souza, Tamires Aparecida [UNESP] (Univ Granada, Fac Political Science & Sociology, 2021)
With this article, we propose to reformulate the Regional Security Complex Theory, by Buzan and Waever, through a South American vision, with the time frame 2008-2016. To this end, we will analyse South America through Argentina, Brazil, and Colombia, and their forms of intra and extra-regional interaction, highlighting the Colombia-United States relations, and the South American Defence Council, of the Union of South American Nations. This article is divided into a first section marked by an understanding of the Regional Complex Theory, in which we present and discuss its theoretical elements and weaknesses, and propose theoretical changes that will guide our analysis. The second section contains information about the South American Complex in the academic view, focusing on the arguments of Buzan and Waever. In the third section, we present the South American Regional Security Complex restructured, as well as the analysis of its dynamics. The central argument of the article is the need to reformulate the Theory in question for a better understanding of the complexities and unique characteristics of South America.
Keywords: Regional Security Complex; South America; Argentina; Brazil; Colombia